Age and growth of the Japanese butterfish Psenopsis anomala in the waters off north-eastern Taiwan. (21st May 2020) - Wang, Shyh-Bin; Hung, Li-Yu; Liu, Kwang-Ming
Abstract: The catch of Japanese butterfish, Psenopsis anomala in Taiwan is greater than those of any other nation; however, the biology, particularly the age and growth, of this economically important fish species is little known. This study describes the age and growth of P. anomala based on 734 specimens (340 females, 363 males, 31 unsexed) caught by trawl fishery in the north-eastern waters off Taiwan from March 2007 to July 2008. The age of specimens was estimated by counting the growth annuli in sagittal otoliths. The periodicity of annulus deposition on otolith was estimated to be one year with opaque zone deposited between July and August based on marginal increment analysis. The maximum age for both sexes was estimated to be 4. The female portion of the population was dominated by the 3 + age class, while the male portion was dominated by the 2∞ age class. The parameters of the von Bertalanffy growth function with standard error estimated based on the observed length at age using a non-linear method are as follows: L ∞ = 25.47 ± 0.65 cm, k = 0.30 ± 0.03 year −1, and t 0 = −1.84 ± 0.16 year for females ( n = 350), and L ∞ = 22.39 ± 0.45 cm, k = 0.46 ± 0.04 year −1, and t 0 = −1.38 ± 0.13 year for males ( n = 378). The growth performances of P. anomala reported from different geographic regions were compared, and the potential influences of sample size distribution on the estimated growth parameters were further discussed.